The unexpected costs of expertise: evidence from highly specialized physicians - Cheng, Yi (Frontiers in Public Health, 2024)
High U.S. spending on health care is commonly attributed to its intensity of specialized, high-tech medical care. A growing body of research focuses on physicians whose medical decisions shape treatment intensity, costs, and patient outcomes. Often overlooked in this research is the assignment of physician skills to patient conditions, which may strongly affect health outcomes and productivity. This matching may be especially important in the case of hospital admissions as high-frequency fluctuations in patient flow make it challenging to maintain effective matches between the best-suited physicians and their patients. This paper focuses on hospitals' responses to demand shocks induced by unscheduled high-risk admissions. I show that these demand shocks result in physician-patient mismatches when hospitals are congested. Specifically, highly specialized physicians who are brought in to treat unscheduled high-risk admissions also treat previously admitted lower-risk patients. This leads to increased treatment intensity for lower-risk patients, which I attribute to persistence in physician practice style. Despite the greater treatment intensity, I find no detectable improvement in health outcomes, which prima facie could be viewed as waste. However, this paper demonstrates that such mismatches mostly happen when the cost of maintaining preferred physicianpatient matching is high, which reflects hospitals' conscientious assessment of costs and benefits and should not be simply interpreted as inefficiency. These findings provide vital information for policymakers looking to identify waste in utilization and create incentives to enhance efficiency in the health care sector.